Able but not willing? Exploring divides in digital versus physical payment use in China. Issue 2 (6th June 2016) - Lloyd, Ashley D.; Antonioletti, Mario; Sloan, Terence M.
Abstract : Purpose: – China is the world's largest user market for digital technologies and experiencing unprecedented rates of rural-urban migration set to create the world's first "urban billion". This is an important context for studying nuanced adoption behaviours that define a digital divide. Large-scale studies are required to determine what behaviours exist in such populations, but can offer limited ability to draw inferences about why. The purpose of this paper is to report a large-scale study inside China that probes a nuanced "digital divide" behaviour: consumer demographics indicating ability to pay by electronic means but behaviour suggesting lack of willingness to do so, and extends current demographics to help explain this. Design/methodology/approach: – The authors report trans-national access to commercial "Big Data" inside China capturing the demographics and consumption of millions of consumers across a wide range of physical and digital market channels. Focusing on one urban location we combine traditional demographics with a new measure that reflecting migration: "Distance from Home", and use data-mining techniques to develop a model that predicts use behaviour. Findings: – Use behaviour is predictable. Most use is explained by value of the transaction. "Distance from Home" is more predictive of technology use than traditional demographics. Research limitations/implications: – Results suggest traditional demographics are insufficient to explain "why" use/non-use occurs and hence an insufficient basis to formulate and target government policy. Originality/value: – The authors understand this to be the first large-scale trans-national study of use/non-use of digital channels within China, and the first study of the impact of distance on ICT adoption.